2007
DOI: 10.1007/s00259-007-0557-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive grading of brain tumours using dynamic amino acid PET imaging : does it work for 11C-Methionine?

Abstract: Unlike FET-PET, the uptake characteristics of MET-PET do not allow classification of low and high grade tumours on an individual patient basis. Since literature data indicate that both tracers have a similar performance regarding biopsy location, tumour delineation, and detection of recurrence, FET-PET should be advocated over MET-PET as its uptake mechanism also allows noninvasive grading in glioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 6 publications
1
37
1
3
Order By: Relevance
“…reported that 11 C-MET PET could be used for the early detection of recurrent brain tumor and for biopsy guidance [13], Zhang et al indicated the usefulness of 11 C-MET PET in the early evaluation of prognosis in patients with bone and soft tissue sarcomas treated by carbon ion radiotherapy [14]. Our clinical study [15] also showed that the SUV max of 11 C-MET was significantly higher in lung cancer than in the pneumoconiotic nodules.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…reported that 11 C-MET PET could be used for the early detection of recurrent brain tumor and for biopsy guidance [13], Zhang et al indicated the usefulness of 11 C-MET PET in the early evaluation of prognosis in patients with bone and soft tissue sarcomas treated by carbon ion radiotherapy [14]. Our clinical study [15] also showed that the SUV max of 11 C-MET was significantly higher in lung cancer than in the pneumoconiotic nodules.…”
Section: Introductionsupporting
confidence: 64%
“…The transport of 11 C-MET into a cell can be followed by rapid metabolization and trapping inside the cell. The exact trapping mechanism is not known but this selective uptake pattern results in a very high tumor-to-background (T/B) ratio enabling the clear delineation of tumors [13]. However, the exact mechanism underlying the accumulation of 11 C-MET in granulomas is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Time-activity curves of high-grade gliomas are characterized by an early peak of 18 F-FET uptake followed by a constant descent, whereas low-grade gliomas and benign brain lesions typically show a steadily increasing curve pattern. In contrast, 11 C-MET PET studies showed no different curve patterns in high-and low-grade gliomas (31).…”
Section: Discussionmentioning
confidence: 78%
“…Investigations of adult brain tumor patients with PET using 11 C-MET and 18 F-FET have reported comparable results for the 2 tracers (10). The evaluation of time-activity curves of 18 F-FET PET uptake may, however, provide valuable additional diagnostic information due to differential kinetic patterns of tracer uptake in high-and low-grade glioma (11-13), a phenomenon not observed with 11 C-MET PET (14). For example, the kinetic pattern of a high-grade glioma appears to be characterized by an early peak after injection within the first 20 min, followed by a decrease of 18 F-FET uptake.…”
mentioning
confidence: 99%